Is Anti-Müllerian Hormone Associated with IVF Outcomes in Young Patients with Diminished Ovarian Reserve?. (March 2016) - Pereira, Nigel; Setton, Robert; Petrini, Allison C; Lekovich, Jovana P; Elias, Rony T; Spandorfer, Steven D
Aim: To investigate whether anti-Müllerian hormone (AMH) is associated with IVF cycle outcomes in young patients with diminished ovarian reserve. Materials & methods: Retrospective study of patients <35 years of age undergoing fresh IVF who had at least two 8-cell, day-3 embryos transferred with grades 1, 1.5 or 2. Patients were subgrouped, a priori, based on serum AMH levels: <1 or >1 ng/ml and <0.5 or >0.5 ng/ml. Results: In total, 1005 patients were included. Patients in the >1 ng/ml group required lesser gonadotropins compared with the <1 ng/ml and the <0.5 ng/ml group. More oocytes were retrieved from the same group compared with the latter two (p < 0.001). Despite these differences, the overall rates of clinical pregnancy, spontaneous abortion and live birth were comparable between the two groups. Conclusion: In patients with diminished ovarian reserve who have good quality embryos, AMH is not associated with clinical pregnancy, spontaneous miscarriage or live birth rates.